A 19 Days Old Neonate with Congenital Pulmonary Airway Malformation: A Case Report - Yadav, Aditya Prakash; Rai, Binod Kumar; Shah, Pankaj Kumar; Raya, Akash; Yadav, Dhirendra Prasad; Kandel, Shiva (Med Phoenix, 2023)
Congenital Pulmonary Airway Malformation (CPAM), previously known as Congenital Cystic Adenomatoid Malformation (CCAM) is a rare dysplastic lesion of the fetal tracheobronchial tree. Here we report a 19 days male child with respiratory distress. Right sided Congenital Pulmonary Airway Malformation Type 1 was diagnosed. Right thoracotomy with upper and middle lobectomy was carried out with successful management of the child.